Leases and the Requirements of Writing. Issue 1 (January 2022) - Webster, Peter
Abstract : This article analyses how the provisions of the Requirements of Writing (Scotland) Act 1995 apply to leases and, in particular, the circumstances in which informally constituted transactions which do not comply with the statutory requirements nevertheless receive legal effect because of the Act's "statutory personal bar" provisions. The subject is of considerable practical importance and also gives rise to basic questions of fairness between contracting parties. However, the relevant provisions of the Act are difficult to apply to leases and the case law is inconsistent. This article proposes a new approach to interpreting the Act which avoids some of the difficulties of the existing decisions and which is more consistent with the legislative intention.